Gambaran pengetahuan stroke pada penderita dan keluarga di RSUP Prof. Dr. R. D. Kandou Manado - Semet, Giovanni R.; Kembuan, Mieke A.H.N.; Karema, Winifred (e-CliniC, 2016)
Abstract: Stroke or circulatory disorders of the brain is a major problem in the field of neurology. Not only the number of events is increasing, but also the possibility of sequel will disturb for a long time. During this time, most people only assume that strokes only occur in adult or old people. In fact, stroke can also occur in adolescents. In Indonesia, it is estimated that each year 500,000 people are affected by stroke, about 2.5% or 125,000 people died, and the rest have mild or severe disabilities. Risk factors for stroke include hypertension, atherosclerosis, high level of cholesterol, heart problems, diabetes, family history of stroke, smoking, aging, unhealthy food, alcohol, less activitiy/exercise, oral contraceptives, obesity, and stress. This was a descriptive study conducted with survey method at Prof. Dr. R. D. Kandou Hospital Manado from November to December 2015. Conclusion: Most respondents consisted of 19 patients and 27 relatives of patients had high level of knowledge of the stroke. Knowledge of stroke patients was higher than their relatives. Keywords: stroke, knowledge of stroke Â  Abstrak: Stroke atau gangguan peredaran darah otak merupakan problem utama dibidang neurologi. Bukan hanya angka kejadiannya yang makin meningkat, tapi juga kemungkinan tersisanya sekuel yang menganggu untuk waktu yang lama. Pendapat umum menganggap bahwa stroke hanya dialami oleh mereka pada usia dewasa atau tua. Padahal stroke juga bisa terjadi pada remaja. Di Indonesia diperkirakan setiap tahunnya terjadi 500.000 penduduk terkena serangan stroke, sekitar 2,5% atau 125.000 orang meninggal, dan sisanya cacat ringan maupun berat. Faktor risiko terjadinya stroke antara lain hipertensi, kolestrol anteriosklerosis, gangguan jantung, DM, riwayat stroke dalam keluarga, merokok, usia, makanan tidak sehat, alcohol, kurang berolaraga, kontrasepsi oral, obese dan stress. Jenis penelitian ialah deskriptif yang dilaksanakan dengan metode survei di RSUP Prof. Dr. R. D. Kandou Manado periode November-Desember 2015. Simpulan: Dari 19 pasien dan 27 keluarga pasien memiliki tingkat pengetahuan yang tinggi terhadap stroke. pengetahuan pada pasien stroke lebih tinggi dari pada keluarga. Kata kunci: stroke, pengetahuan mengenai stroke